PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Purnamasari, Melinda; Yuniarwati, Yuniarwati (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to empirically prove the effect of profitability, leverage, and firm size on tax avoidance in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Based on the purposive sampling technique, 23 companies were obtained with a total of 115 samples for five years. The analytical method used in this study is multiple linear regression analysis, then processed with the eviews version 12 program. The results of this study indicate that profitability and firm size have a negative and significant effect on tax avoidance, while leverage has a negative and insignificant effect on tax avoidance.